2022
DOI: 10.3390/ijms23084417
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cardiotoxic Effects of Lead Intoxication in Rats Induced by Muscular Exercise

Abstract: Exposure to lead is associated with an increased risk of cardiovascular diseases. Outbred white male rats were injected with lead acetate intraperitoneally three times a week and/or were forced to run at a speed of 25 m/min for 10 min 5 days a week. We performed noninvasive recording of arterial pressure, electrocardiogram and breathing parameters, and assessed some biochemical characteristics. Electrophoresis in polyacrylamide gel was used to determine the ratio of myosin heavy chains. An in vitro motility as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Klinova et al conducted an in vivo study to examine the cardiotoxic effect of Pb acetate. They administered a dose of 11 mg/kg body weight intraperitoneally over a 6-week period, three times a week, and discovered a significant reduction in the maximal velocity of reconstituted thin filament sliding over rat myosin under lead intoxication [ 31 ]. Gerzan et al exposed male rats to intraperitoneal doses of 12.5 mg of Pb per kg body mass and 6.01 mg of Pb per kg body mass over a five-week period.…”
Section: Discussionmentioning
confidence: 99%
“…Klinova et al conducted an in vivo study to examine the cardiotoxic effect of Pb acetate. They administered a dose of 11 mg/kg body weight intraperitoneally over a 6-week period, three times a week, and discovered a significant reduction in the maximal velocity of reconstituted thin filament sliding over rat myosin under lead intoxication [ 31 ]. Gerzan et al exposed male rats to intraperitoneal doses of 12.5 mg of Pb per kg body mass and 6.01 mg of Pb per kg body mass over a five-week period.…”
Section: Discussionmentioning
confidence: 99%
“…Pb, whose increased concentration in the left ventricle was noted by Ćirović et al [ 150 ], was identified as severely cardiotoxic in an animal study [ 151 ]. In detail, Klinova et al, observed higher levels of angiotensin-converting enzyme (ACE) and an amplified T-wave amplitude during an electrocardiograph examination.…”
Section: The Role Of Trace Elements In Selected Cardiovascular Diseasesmentioning
confidence: 99%
“…In detail, Klinova et al, observed higher levels of angiotensin-converting enzyme (ACE) and an amplified T-wave amplitude during an electrocardiograph examination. In addition, the cardiomyocyte thickness of the lead-exposed group (5.38 ± 0.12 μm) was found to be higher than that of the control group (4.74 ± 0.08 μm); although this difference was relatively small, it was still statistically significant ( p < 0.01) [ 151 ]. Moreover, they recorded a reduction in the maximal velocity of thin filament slide over myosin, leading to a reduced contraction of the cardiomyocytes.…”
Section: The Role Of Trace Elements In Selected Cardiovascular Diseasesmentioning
confidence: 99%
“…Knowledge on the cellular mechanisms underlying heavy metal-induced cardiotoxicity is primarily documented through in vivo experiments (22,23) and in vitro studies (10,24). Gerzan et al exposed male rats to lead acetate three times a week over a span of 35 days, demonstrating that lead impaired the mechanical characteristics of myosin in both the atria and ventricles (23).…”
Section: Metal(loid) Induced-cardiotoxicitymentioning
confidence: 99%